Impact of tigecycline versus imipenem–cilastatin on fibrinogen levels following cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC): a randomized-controlled study. (19th May 2018) - Hakeam, Hakeam A.; Al Duhailib, Zainab; Salahuddin, Nawal; Amin, Tarek
Abstract : The aim of this prospective, randomized study was to compare the effects of tigecycline and imipenem-cilastatin on fibrinogen levels in patients undergoing cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). Patients were empirically randomized to receive tigecycline or imipenem–cilastatin. Fibrinogen levels were measured in both patient groups on days 1, 3, 5 and 8 of antibiotic therapy and 3 days after antibiotic therapy completion. Twenty patients received tigecycline and 22 patients received imipenem–cilastatin . Patients in the tigecycline group had lower mean fibrinogen levels compared to those in the imipenem–cilastatin group on day 3 (4.1 ± 1.2 vs. 5.9 ± 1.3 g/L; p  < 0.001), day 5 (3.7 ± 1.2 vs. 6.5 ± 1.1 g/L; p  < 0.001), day 8 (3.5 ± 1.3 vs. 5.8 ± 1.6 g/L; p  < 0.001), and day 3 after antibiotic completion (4.1 ± 1.4 vs. 6.1 ± 1.6 g/L; p  < 0.001). In conclusion, compared to imipenem–cilastatin, tigecycline was associated with a significant decrease in fibrinogen levels, following CRS and HIPEC.